2017
DOI: 10.1128/mbio.02312-16
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Pseudomonas aeruginosa PAO1 DNA Methyltransferase, Its Targets, and Physiological Roles

Abstract: DNA methylation is widespread among prokaryotes, and most DNA methylation reactions are catalyzed by adenine DNA methyltransferases, which are part of restriction-modification (R-M) systems. R-M systems are known for their role in the defense against foreign DNA; however, DNA methyltransferases also play functional roles in gene regulation. In this study, we used single-molecule real-time (SMRT) sequencing to uncover the genome-wide DNA methylation pattern in the opportunistic pathogen Pseudomonas aeruginosa P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 64 publications
1
43
0
Order By: Relevance
“…SMRTseq takes advantage of the effects of base modifications in the DNA template on the kinetics of incorporation of complementary nucleotides, to infer DNA methylation events [28]. This technique has been validated in a number of unicellular species [30,31,[43][44][45][46] and we and others, used SMRTseq to map 6mA events in metazoa [10,13,15,20,30,47]. SMRTseq is appealing because it provides an independent method for validating the presence of 6mA and can identify modified bases in their sequence context at nucleotide resolution.…”
Section: Smrtseq Overestimates 4mc In Bacteriamentioning
confidence: 99%
“…SMRTseq takes advantage of the effects of base modifications in the DNA template on the kinetics of incorporation of complementary nucleotides, to infer DNA methylation events [28]. This technique has been validated in a number of unicellular species [30,31,[43][44][45][46] and we and others, used SMRTseq to map 6mA events in metazoa [10,13,15,20,30,47]. SMRTseq is appealing because it provides an independent method for validating the presence of 6mA and can identify modified bases in their sequence context at nucleotide resolution.…”
Section: Smrtseq Overestimates 4mc In Bacteriamentioning
confidence: 99%
“…1a). Interestingly, two mutations identified in PAO1161 in comparison to PAO1-UW, that resulted in an introduction of premature stop codons mapped to PA2735 gene, recently shown to encode a N6adenosine DNA methyltransferase acting on a conserved sequence GATC(N) 6 GTC [50,51], and PA1939, encoding a putative overcoming lysogenization defect Table 1 SNPs and indels identified in P. aeruginosa PAO1161 genome, resulting in expression of truncated proteins. The effect of a mutation is predicted using the PAO1-UW genome as a reference.…”
Section: Analysis Of Pao1161 Revertants In Pa1939 and Pa2735mentioning
confidence: 99%
“…We previously demonstrated that the wild-type Pseudomonas aeruginosa PAO1 can be freeze-dried and rehydrated so that their metabolism generates power (Figure 5c) [29]. Furthermore, our recent literature survey indicates that P. aeruginosa can produce protecting proteins under oxidative stress such as freezedrying (Figure 5b) [37,38], which will probably improve their survival rate during the process. The rehydration of freeze-dried exoelectrogens is a critical step for on-demand power generation [39].…”
Section: Freeze-drying Bacterial Cellsmentioning
confidence: 98%